Cultural intelligence in higher education: Promoting inclusion and global collaboration - Marina Sousa (Societal Impacts)
Cultural intelligence (CQ) is becoming increasingly recognized as a vital skill in the contemporary globalized context, particularly within the domain of higher education. This study examines the impact of CQ on society, with a particular focus on its importance in promoting inclusion and global collaboration. A quantitative approach was employed in the study, which applied the Cultural Intelligence Scale (CQS) to 445 participants, comprising students and teachers, with the objective of assessing the four dimensions of CQ: metacognitive, cognitive, motivational and behavioral. The findings indicated that the participants exhibited high levels of CQ, particularly in the motivational, metacognitive, and behavioral dimensions. However, they demonstrated lower performance in the cognitive dimension. The results demonstrated a significant correlation between international experience, cultural exposure and language fluency and higher levels of CQ. The study emphasizes the pivotal role of higher education institutions (HEIs) in fostering CQ through targeted programs and intercultural experiences, equipping students with the skills to navigate a globalized world. The implications extend from the development of multicultural curricula to the formulation of public policies that promote inclusion and diversity, contributing to a more cohesive and peaceful society – a more culturally intelligent society.